Man's cosmic bonds: Iqbal's insights on universe, nature, and environment - Abdul Razak, Mohd Abbas; Laluddin, Hayatullah (Mission Soft Foundation, 2023)
The debate on man and nature is one that has been going on for many centuries. One should not be surprised that even today scientists and other researchers are still conducting studies in the area of man and nature. Before we go to the central theme of this essay on Iqbal, the authors would like to draw your attention to words like; universe, nature and environment. The clarification of these three entities is deemed important by the authors for the reason, that Muhammad Iqbal (1877-1938) states them in his Reconstruction (1996) and poems relating to his theory on personality development in man. Many would agree that the three entities that refer to a reality that exists outside of man, are used interchangeably as if they meant to be the one and the same thing. It is important to state that although they are entities outside of man, nevertheless, man has to interact with them in order to fulfil the mission for which he has been sent to this world by Allah SWT. Being synonymous with one another, the three worlds only differ in their contextual use. To prove the case, when people hear the word universe, it is quite natural for them to imagine a sky above them laden with planets and billions of stars that illuminate the night sky. Having said that, we are pretty sure one will never be looking at the ground on which he/she is standing while thinking of the universe. Likewise, the word nature draws a mental picture in people's minds of the flora and fauna. Finally, the word environment draws people’s attention to the immediate surroundings in which they live.